An inflammatory Signature of Glucose Impairment in Cystic Fibrosis - Montemari AL; Manco M; Fiocchi AG; Bartoli M; Facchiano F; Tabolacci C; Scatigna M; Ciciriello F; Alghisi F; Montemitro E; Carsetti R; Lucidi V; et al. (Dove Medical Press, 2022)
Anna Lisa Montemari,1 Melania Manco,2 Alessandro Giovanni Fiocchi,3 Manuela Bartoli,4 Francesco Facchiano,5 Claudio Tabolacci,5 Maria Scatigna,6 Fabiana Ciciriello,3 Federico Alghisi,3 Enza Montemitro,3 Rita Carsetti,7 Vincenzina Lucidi,3 Ersilia Vita Fiscarelli1 1UOS Cystic Fibrosis Diagnostic, UOC Microbiology and Immunology Diagnostic, Bambino Gesù Children’s Hospital, IRCCS, Rome, Italy; 2Research Area for Multifactorial Diseases, Bambino Gesù Children’s Hospital, IRCCS, Rome, Italy; 3Cystic Fibrosis Unit, Department of Pediatrics Bambino Gesù Children’s Hospital, IRCCS, Rome, Italy; 4Department of Ophthalmology, Medical College of Georgia, Augusta University, Augusta, GA, USA; 5Department of Oncology and Molecular Medicine, Istituto Superiore Di Sanità, Rome, Italy; 6Department of Life, Health and Environmental Sciences, University of L’Aquila, L’Aquila, Italy; 7Diagnostic Immunology Unit, Department of Laboratories, B Cell Pathophysiology Unit, Immunology Research Area, Bambino Gesù Children’s Hospital, IRCCS, Rome, ItalyCorrespondence: Melania Manco, Bambino Gesù Children’s Hospital, IRCCS, piazza Sant’Onofrio 4, Rome, Italy, Tel +39 06 6859 2649, Fax +39 06 6859 2904, Email melania.manco@opbg.netObjective and Design: Cystic fibrosis-related diabetes (CFRD) is a severe complication associated with increased morbidity and mortality in cystic fibrosis (CF) patients. Extensive inflammatory state in CF leads to pancreas damage and insulin resistance with consequent altered glucose tolerance and CFRD development. The aim of the present study was to identify circulating levels of inflammatory markers specifically associated with impaired glucose tolerance (IGT) and overt CFRD in a sample of young adults with CF.Materials and Methods: Sixty-four CF outpatients, without evident active pulmonary exacerbation, infectious and autoimmune diseases, were enrolled in the study and the levels of 45 inflammatory serum mediators were measured through x magnetic bead panel multiplex technology.Results: Serum levels of PDGF-AA, CCL20/MIP3α, IFNα, CCL11/eotaxin, CXCL1/GROα, GMCSF, B7H1/PDL1, IL13, IL7, VEGF, and TGFα were all significantly (p< 0.05) elevated in patients according to glycemic status and directly correlated with glycated hemoglobin and C-reactive protein levels.Conclusion: Our findings suggest that increased levels of specific circulating inflammatory mediators are directly associated with impaired glucose tolerance in CF patients, thus, potentially implicating them in CFRD pathogenesis and warranting larger longitudinal studies to validate their monitoring as predictor of CFRD onset.Keywords: cystic fibrosis-related diabetes, cytokines, growth factors, immune mediators, impaired glucose tolerance, inflammation